ESPACIALIZAÇÃO DE INUNDAÇÕES EM GOIÂNIA (GO) (2004-2007) - Kesia Rodrigues dos Santos; Patrícia de Araújo Romão (Boletim Goiano de Geografia)
This paper was accomplished in Goiânia the state of Goiás. To achieve the objective of this work, which was toidentify the places of occurrence of inundation in Goiânia and spatialise them, were delineated areas of occurrenceof inundation in urban area, through the collection of information contained in articles in local newspapersand data from the Civil Defense. The information contained in these sources were relevant not only for locationsof occurrence of events and to check what are the areas with recurrent events, and therefore more problematic.Stand out neighborhoods close to the Meia Ponte river and Guanabara II garden on the banks of the streamPedreira, such as those appearing in more headlines. In relation to the concentration of sites of occurrence ofinundation the large concentration of events occurs in the southern portion of Goiania which appears largelyurbanized, and sealed with the drainage changed. The remaining points are associated with Anicuns, Meia Ponteand João Leite in smaller proportions. In addition to these sites appear Pedreira stream, the stream Água Brancaand some points regarded as floods, because they are not associated with watercourses.